Pronounced limb and fibre type differences in subcellular lipid droplet content and distribution in elite skiers before and after exhaustive exercise - Koh, H.-C. E.; Nielsen, J.; Saltin, B.; Holmberg, H. C.; Ørtenblad, N. (The Journal of Physiology, 2017)
Key points